Media Pembelajaran Berbasis Autoplay Media Studio untuk Siswa SMP - Ian Rizky Maulana; Sapto Adi; Eko Hariyanto (Graduate School of Universitas Negeri Malang, 2019)
Abstract: The purpose of this research and development is to produce a physical education learning product for large ball material for 7th grade junior high school. The development of physical education for large ball material for 7th grade junior high school researchers used a multimedia development model developed by Lee & Owen. The results of the study on the validation of physical education learning experts obtained a percentage of 76.12% is quite valid, quite effective, quite complete, can be used but need minor improvements. The results of the research on material expert validation obtained a percentage of 94.70% very valid. While the overall average of media expert validation obtained a percentage of 94.38% is very valid. For small group trials conducted by distributing questionnaires to 20 students of Lumajang Middle School 5. The results of small group trials found that the average percentage of 94.63% was very valid. The large group trial was conducted by distributing questionnaires to 90 students of SMP Negeri 1 Lumajang, SMP 1 Sukodono and SMP Negeri 5 Lumajang. The results of a large group trial found that the average percentage of 90.02% was very valid. Overall, the research and development products are very valid and can be used as learning media.Abstrak: Tujuan penelitian dan pengembangan ini adalah untuk menghasilkan sebuah produk pembelajaran Pendidikan Jasmani materi bola besar untuk SMP kelas VII. Pengembangan pembelajaran Pendidikan Jasmani materi bola besar untuk SMP kelas VII, peneliti menggunakan model pengembangan multimedia yang dikembangkan oleh Lee & Owen. Hasil penelitian pada validasi ahli pembelajaran Pendidikan Jasmani diperoleh persentase 76,12% cukup valid, cukup efektif, cukup tuntas, dapat digunakan namun perlu perbaikan kecil. Hasil dari penelitian pada validasi ahli materi diperoleh persentase 94,70% sangat valid. Rata-rata keseluruhan dari validasi ahli media diperoleh persentase 94,38% sangat valid. Uji coba kelompok kecil dilakukan dengan penyebaran kuesioner kepada 20 siswa SMP Negeri 5 Lumajang. Hasil dari uji coba kelompok kecil didapat persentase rata-rata sebesar 94,63% sangat valid. Uji coba kelompok besar dilakukan dengan penyebaran kuesioner kepada 90 siswa SMP Negeri 1 Lumajang, SMP Negeri 1 Sukodono dan SMP Negeri 5 Lumajang. Hasil dari uji coba kelompok besar didapat persentase rata-rata sebesar 90,02% sangat valid. Secara keseluruhan, produk penelitian dan pengembangan ini sangat valid dan dapat digunakan sebagai media pembelajaran.